New Subclasses of Meromorphically Uniformly of Multivalent Functions with Positive and Fixed Second Coefficients - Aljuboori, O. M.; Jassim, Kassim A. (Iraqi Journal of Science, 2023)
In this paper, we consider new subclasses     of meromorphic uniformly of multivalent functions in    with fixed second coefficient, we obtain the estimation of coefficients, distortion theorems, closure theorems and some other results.